In vivo Anti-diabetic and Anti-hyperlipidemic Activities of ethyl Acetate/Methanol Fractions of Feronia elephantum Fruit in type 2 Diabetic Rats: Via α-amylase and PPAR-γ by using in silico Approach - Reddy, Gangavaram Jyothi; Reddy, Kesavan Bhaskar; Reddy, Gopireddy Venkata Subba (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Obesity and overweight, together with physical inactivity, are projected to cause a huge proportion of the global diabetes burden. Natural products play a key role in the discovery of novel therapeutic agents. Aim: The present study aimed to elucidate in silico and in vivo anti-diabetic and anti-hyperlipidemic potential of Ethyl acetate (EFE) and ethyl acetate:methanol (EMFE) fractions of F. elephantum fruit in diabetic rats. Methods: Male Sprague-Dawley rats were induced type 2 diabetes by high fat diet (HFD) for a period of 2 weeks and then injected intraperitoneally with Streptozotocin (STZ, 35 mg/ kg b.w). Results: Significant antihyperglycemia was displayed in rats treated with EFE and EMFE in OGTT in normal rats. Daily oral treatment with EFE and EMFE each at 100 and 200 mg/kg b.w for 5 weeks resulted in significant reduction in plasma glucose levels and HbA1c, increased plasma insulin levels, normalised lipid profile and liver function parameters in HFD and STZ model. In addition, degenerative histopathological changes were found to be normalized. Molecular docking studies revealed strong binding efficacy of the active constituents of the extract viz., 22,23-dihydrostigmasterol, tocopherol and campesterol with α-amylase enzyme and PPAR-γ. Conclusion: These results suggest a promising anti-diabetic and anti-hyperlipidemic effect of Feronia elephantum fruit without apparent toxic effects.
Keywords: Molecular Docking; Feronia elephantum; Anti-diabetic; Anti-hyperlipidemic; Streptozotocin; High Fat Diet